Gender Analysis of Ornamental Fish Production Units in Maharashtra, India - Yadav, Bharat; Sharma, Arpita (Frontiers in Marine Science, 2022)
Ornamental fisheries are an emerging business and offer vast opportunities. In India, the Maharashtra state had a scheme called “Rainbow Revolution”, which was started to encourage breeding and export of ornamental fishes. Taking advantage of this scheme, 305 male and female entrepreneurs took up this small-scale business. Gender analysis, which provides the necessary data and information to integrate a gender perspective into policies, programs, and projects and allows for the development of interventions that address gender inequalities, was conducted using the Harvard Analysis Framework for male and female entrepreneurs involved in ornamental fish production. The objectives were to explore factors that influenced entrepreneurs to take up this business and to map the activity, access, and control profile of male and female entrepreneurs involved in ornamental fish production. Out of 305 ornamental production units under the Rainbow Revolution scheme, 110 units were studied, of which 82 were owned by men and 28 were owned by women. Factors that influenced both men and women to pursue this business were community norms, prevailing social hierarchy, demographic factors, and access to special training. Activity profile revealed that men were involved in the construction of ornamental fish production unit, observation and checking fish health, checking water parameters, live food culture, marketing, upkeep, and maintenance, and it was found that they spent an average of 8 h/day on these activities. Women were involved in fish feeding, cleaning of tanks, siphoning, feed preparation, and marketing, spending an average of 4 h/day. Many activities like feeding, cleaning of tanks and siphoning, feed preparation, setting of fish for breeding, removal of offspring, and marketing were performed by both. Men had higher access and control on resources like land, farm, machine, equipment, and finances. The Mann–Whitney U test revealed a statistically significant difference between men and women’s access and control on resources. A study has revealed that in addition to family and house responsibilities, women spent 4 h/day on this business. They have less access and control on resources because of the existing power relations with which we conclude that men and women cannot be treated as homogeneous categories when designing any schemes/policy interventions.